CLINICAL-EPIDEMIOLOGICAL EPILEPSY CHARACTERISTICS IN TRANSBAIKALIA - Yu. A. Kritskaya; N. A. Shnayder; Yu. A. Shirshov (Эпилепсия и пароксизмальные состояния, 2016)
The epidemiological study of epilepsy in the Transbaikal region, using the homestead bypass in representative samples of adults (14 years and older) was developed. We studied the prevalence and incidence, social and etiological aspects of epilepsy. Found that the prevalence of epilepsy among rural and urban population is 3,66 and 3,46 cases per 1,000 population, and incidence – 21,59 and 20,71 cases per 100,000 persons per year, respectively. According to these indicators Transbaikalia approaching to national level.